Patriarchal ideology, Andrew Tate, and Rumble’s podcasts - Sayogie, Frans; Farkhan, Muhammad; Zubair; Julian, Hendrio Putra; Al Hakim, Hilman Syauqiy Fauza; Wiralaksana, Muhammad Guntur (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study aimed to examine public responses to patriarchal ideology through language, as expressed by Andrew Tate on the fringe platform Rumble. Rumble is generally known for hosting far-right content, serving as a refuge for public figures who have been de-platformed from mainstream social media. This study used a combination of netnographic and archival data collection with attitudinal appraisal theory to evaluate public responses. The comment sections of four podcast videos by ‘TateSpeech’ on Rumble were selected as the primary data source. Analysis of the affect, judgment, and appreciation of the public regarding the patriarchal ideology of Andrew Tate was then carried out. The results showed that the majority of the public comments towards the videos were positive. The deplatforming of Andrew Tate triggered the Streisand effect, resulting in a seeming increase in his level of support after his removal from mainstream social media. Based on these findings, this study concluded that the patriarchal ideology was expressed in an attempt to increase online reach by manipulating social media language content to attract more followers, particularly the young male audience.